Factors associated with understanding and perineal wound care behavior of postpartum mothers in Cikeusik district, Pandeglang regency - Kurnia, Nia Marlina; Rahayu, Antika Maulida; Shobah, Afifah Nur (Institute of Computer Science (IOCS), 2024)
Maternal deaths after childbirth occur when perineal wounds are common in women after childbirth, either vaginally or by caesarean section. This wound can cause pain, discomfort, and potentially lead to infection if not treated properly. Proper care of perineal wounds in accordance with the recommendations of health workers is very important to accelerate the healing process and prevent complications. The purpose of this study was to determine the relationship between factors with knowledge and behavior of perineal wound care in postpartum women in Cikeusik District Pandeglang-Banten. This study used quantitative research with a cross sectional design based on analysis using chi square statistical test >0.05, known p value 0.00 for variable debriefing, p value 0.01 for variable parity and p value 0.02 for variable age. Conclusion There is a significant relationship between age, parity and debriefing factors with understanding and behavior of perineal wound care.